2014
DOI: 10.1089/bio.2013.0056
|View full text |Cite
|
Sign up to set email alerts
|

Biobanking Practice: RNA Storage at Low Concentration Affects Integrity

Abstract: A critical issue in defining protocols for biobanking practices is the preservation of total RNA for assessing the whole transcriptome and ensuring that it can be utilized in clinically oriented studies. Storage conditions, such as temperature and the length of time that tissues and purified RNA stay frozen, may directly impact RNA preservation. In this study, we evaluated a) the quality of RNA (as measured by RNA Integrity Number) purified from head and neck tumor tissues stored at -140°C for distinct time in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Preanalytical storage factors affecting analyte quantity, quality, or gene expression are temperature, storage time, concentration of RNA, and repeated thaws (53,119,120 ). As for RNA, new technologies for dry storage at room temperature have been developed (121)(122)(123).…”
Section: Rnamentioning
confidence: 99%
“…Preanalytical storage factors affecting analyte quantity, quality, or gene expression are temperature, storage time, concentration of RNA, and repeated thaws (53,119,120 ). As for RNA, new technologies for dry storage at room temperature have been developed (121)(122)(123).…”
Section: Rnamentioning
confidence: 99%
“…16,17 Whether tissue should be stored at -80°C or -140°C remains unclear. 13,23 We observed no adverse effects on RNA quality in fresh-frozen tissue after storage at -80°C for up to 6 years.…”
Section: Discussionmentioning
confidence: 67%
“…In theory, tissues that are quickly frozen and kept below this temperature are free of any degradation of macromolecules (e.g., hydrolysis or enzymatic degradation) [9][10][11]. In a recent study, our group showed no significant change in RIN (RNA Integrity Number) values of cryopreserved tissues stored at −140°C for up to 7 years [12]. On the other hand, researchers at the Indiana University, examining sets of samples that were stored at −80°C observed that all samples with less than 18 months of storage had high-quality RNA (also analyzed by RIN), compared to only 48% of the samples that were stored for longer periods (>8 years) [8].…”
Section: Tissue Collection and Storage Requirementsmentioning
confidence: 72%
“…In the same study in which our group analyzed the storage conditions of tissues, the long-term preservation of RNA molecules was also addressed. With respect to RNA aliquots (which are stored at −80°C), our results shown that the concentration of stored RNA strongly affects its integrity in long-term storage, indicating that biobanks that intend to distribute not only tissues, but also extracted RNA macromolecules for research must also control this variable, storing RNA in high concentration (>200 ng/μl) [12].…”
Section: Quality Assurance -Histology and Molecular Aspectsmentioning
confidence: 89%
See 1 more Smart Citation